2021
DOI: 10.1007/s12325-021-01998-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Ropeginterferon Alfa-2b in the Off-Label Use for the Treatment of COVID-19 Patients in Taiwan

Abstract: Introduction This study, for the first time to our knowledge, evaluated the efficacy of ropeginterferon alfa-2b, a long-acting pegylated interferon (IFN)-alfa, in the treatment of COVID-19. Methods We retrospectively evaluated ropeginterferon alfa-2b administered subcutaneously at a single dose of 250 µg for the treatment of mild and moderate COVID-19. Primary outcome was to compare the overall negative conversion time from the confirmed, last positive SARS-CoV-2 RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition, it was used as an off-label treatment for other indications. [22][23][24] The data from this Phase 3 study showed that in the clinical viral hepatitis C genotype 2 setting, ropeginterferon alfa-2b was efficacious, meeting the primary endpoint of non-inferiority to the weekly given, conventional pegylated IFN alfa-2b, previously approved for the CHC treatment. The ropeginterferon alfa-2b group also had numerically better virologic responses consistently in every time point of the measurements during the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was used as an off-label treatment for other indications. [22][23][24] The data from this Phase 3 study showed that in the clinical viral hepatitis C genotype 2 setting, ropeginterferon alfa-2b was efficacious, meeting the primary endpoint of non-inferiority to the weekly given, conventional pegylated IFN alfa-2b, previously approved for the CHC treatment. The ropeginterferon alfa-2b group also had numerically better virologic responses consistently in every time point of the measurements during the study.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first approved IFN‐based therapy for an MPN by the US FDA. In addition, it was used as an off‐label treatment for other indications 22–24 …”
Section: Discussionmentioning
confidence: 99%
“…Type I interferons (IFN) was proposed to be a treatment option against SARS-CoV-2 infection by activating both cellular and humoral immunities. [5][6][7][8][9] In vitro and cohort clinical studies with small case numbers showed potential benefits with type I IFN treatment [6,[9][10][11]. Ropeginterferon alfa-2b is a site-selective PEGylated proline-IFN alfa-2b [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was approved as the first IFN-based therapy for adult patients with polycythemia vera in Europe and the US, and is currently under clinical development for viral infection, including hepatitis B and C [16][17][18][19][20][21][22]. As for SARS-CoV-2 infection, a retrospective study by Chen et al demonstrated that ropeginterferon alfa-2b in combination with standard of care (SOC) was associated with a more rapid viral clearance than SOC alone in patients with moderate SARS-CoV-2 infection [7]. In this multi-centered, open-labeled, randomized, phase 3 study, we aimed to evaluate the efficacy and safety of ropeginterferon alfa-2b for the treatment of patients with moderate SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…The safety of ropeginterferon alfa-2b was also evaluated in patients with chronic hepatitis B or hepatitis C (genotypes 1 and 2) at doses ranging from 270 to 450 mcg every 2 weeks as monotherapy or in combination with ribavirin (23)(24)(25)(26)(27), or in COVID-19 patients in combination with standard of care at 250 mcg (28). Most reported adverse events (AEs) during ropeginterferon alfa-2b treatment were mild or moderate and toxicities ≥grade 3 were uncommon.…”
Section: Introductionmentioning
confidence: 99%